2020
DOI: 10.1109/tro.2019.2956870
|View full text |Cite
|
Sign up to set email alerts
|

TWISTER Hand: Underactuated Robotic Gripper Inspired by Origami Twisted Tower

Abstract: This article presents a new cable-driven underactuated robotic gripper, called TWISTER Hand. It is designed for adaptable grasping of objects in different shapes, weights, sizes, and textures. Each finger of the gripper is made of a compliant and continuum mechanism inspired by an origami design. This design is converted into a computer-aided design (CAD) model and 3-D printed using flexible and rigid polymer composite materials. Two CAD modeling methods for this design are compared in terms of structural stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 58 publications
0
41
0
2
Order By: Relevance
“…• Gripper could lift 100 times its own weight with great ease • Could withstand a maximum force of 40 N actuated system for driving the actuators where one single motor was connected to three cables, each cable passing through a single finger [25]. In contrast to this underactuated gripper, Chen et al developed a gripper with three fingers, each actuated by a separate motor.…”
Section: Cable-driven Actuationmentioning
confidence: 99%
See 1 more Smart Citation
“…• Gripper could lift 100 times its own weight with great ease • Could withstand a maximum force of 40 N actuated system for driving the actuators where one single motor was connected to three cables, each cable passing through a single finger [25]. In contrast to this underactuated gripper, Chen et al developed a gripper with three fingers, each actuated by a separate motor.…”
Section: Cable-driven Actuationmentioning
confidence: 99%
“…(2015) [25] Application: soft surgical robot 1. Manipulator was divided into two parts; each part driven by four cables 2.…”
Section: Shape Memory Alloy Actuationmentioning
confidence: 99%
“…Similarly, a soft pneumatic gripper with a tendon driven soft origami pump was built using a Kresling pattern ( Kim et al, 2020 ), which is similar to PFP. Another pattern similar to PFP, i.e., stacked octagonal layers by Mihoko Tachibana was used to create an under actuated robotic gripper; TWISTER Hand ( Lee et al, 2020 ). Martinez et al (2012) reported programmable paper-elastomeric composites origami, where a paper-based bellows origami pattern (similar to PFP) was molded with elastomeric material to prototype an elongating actuator.…”
Section: Principle Of Designmentioning
confidence: 99%
“…A picking robot arm is scheduled to pick a task in the specific working space to enhance the stability and movement with a specific trajectory points [8]. In [9], the authors have presented a cable-driven underactuated robotic gripper, which is designed for adaptable picking objects in different shapes, weights, sizes, and textures. ABB's Yumi robot has been reported many successful efforts to improve dual-arm operations for synchronized programming in industrial tasks detailed in [3].…”
Section: Introductionmentioning
confidence: 99%